Effect of Structured Counselling on Women's Ch< oice of Anaesthesia for Elective Repeat Caesarean Section (ERCS) At Abbasi Shaheed Hospital: A Cross Sectional Comparative Survey - Rahila Imtiaz; Samia Husain; Rubina Izhar (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To evaluate the effect of structured counselling on women's choice of obstetrical anaesthesia for elective caesarean section. Methods: This was a cross-sectional comparative survey conducted at department of gynaecology (unit II), Abbasi Shaheed Hospital, Karachi, from 1st January, 2017 to 30th June, 2017. The study included 250 pregnant women at term ( ³37 weeks) with a prior caesarean section, planned for elective caesarean having no contraindications to spinal or general anaesthesia. Excluded from the study were women with obstetric emergencies like antepartum haemorrhage, cord prolapse, eclampsia, disseminated  intravascular  coagula-  tion, vertebral column deformities, foetal distress and obstructed labour. They were asked about the technique of anaesthesia they would prefer for their caesarean section. The women then received structured counselling  and  the  choice  was  assessed  again.  Chi-square  statistic  was  applied  to  assess  the   association between both choices taking p-value of £ 0.05 as statistically significant. Data were analysed using the SPSS software program, version 15.0 (IBM, Armonk, USA). Results: Out of 250 women recruited, before counselling 116  (46.4%)  chose  general  anaesthesia,  94  (37.6%) women chose spinal anaesthesia whereas 40 (16%) had no particular preference. After receiving structured counselling 68 (27.2%) women chose general, 170 (68%) women opted for spinal and 12 (4.8%) women still remained undecided. The effect of structured counselling was assessed by cross-tabulating pre- counselling choice and post-counselling choice. The Chi-square test statistic was significant at p  < 0.001 showing a significant association of structured counselling on the choice of anaesthesia. Conclusion: Women's choice is significantly altered by the counselling. Majority of  women's  beliefs  are  shaped by past experience and the information they  receive.  Significant  improvement  can  be  expected in near future if more consistent information is provided. Consistency can be ensured by use of patient informa-  tion leaflets.